2012
DOI: 10.1016/j.fuel.2011.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Reactive DWC leading the way to FAME and fortune

Abstract: a b s t r a c tReactive separation processes were recently proposed for the synthesis of fatty acid methyl esters (FAMEs), most of them making use of solid catalysts thus eliminating all conventional catalyst-related operations, improving process efficiency and reducing energy requirements. Such integrated systems require a stoichiometric reactants ratio in order to achieve complete conversion and high purity products. However, maintaining this ratio can be very difficult in practice, especially when the fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…It is calculated that the DWC-DME process leads to 44.53 % reduction in operating costs, compared to the classic DME production unit. This saving is in a fair agreement with the A c c e p t e d M a n u s c r i p t 11 researchers findings for the DWCs schemes [9][10][11][12][13][14][15]25]. Figure 7 shows the composition profiles in both sides of the wall.…”
Section: Simulation Of the Dwc-dme Unitsupporting
confidence: 89%
See 2 more Smart Citations
“…It is calculated that the DWC-DME process leads to 44.53 % reduction in operating costs, compared to the classic DME production unit. This saving is in a fair agreement with the A c c e p t e d M a n u s c r i p t 11 researchers findings for the DWCs schemes [9][10][11][12][13][14][15]25]. Figure 7 shows the composition profiles in both sides of the wall.…”
Section: Simulation Of the Dwc-dme Unitsupporting
confidence: 89%
“…By process integration, the feed components can be distilled and separated with a small amount of utilities consumption [7,8]. The main advantage of a DWC is its possibility in saving both energy and capital costs [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The theoretical studies have shown that DWCs save at least 30 % of energy costs compared to the conventional schemes [7][8][9].…”
Section: Page 3 Of 29mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, stochastic optimisation methods are easy to implement and do not require the calculation of derivatives of the objective function, making the optimisation procedure very robust, which is especially advantageous for the optimisation of largescale, nonlinear, nonconvex problems. The two most important examples of stochastic algorithms that were used to optimise RD processes are the simulated annealing method (Cardoso et al, 2000;Gomez et al, 2006;Kiss et al, 2012) and evolutionary algorithms (Babu and Khan, 2007;Rahman et al, 2008;Urselmann et al, 2011). An evolutionary algorithm was applied in the present work to optimise the RD column described in Section 2.2 towards EMC or DEC selectivity while still having high reactant conversions.…”
Section: Optimisationmentioning
confidence: 99%
“…In this publication, the specific details for this connection were not shown. Although other authors have also used this integration between Aspen Plus and Matlab (Kiss et al, 2012;Vázquez-Ojeda et al, 2013), no specific information can be found on the web or in the Aspen Customer support web page. This paper describes a detailed protocol for using the Aspen Plus user interface for calling Matlab user models.…”
Section: Introductionmentioning
confidence: 99%